PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR TEMATIK KELAS IV SDN 35 PONTIANAK SELATAN - yarso, Agustini; Kresnadi, Hery; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is aims to describe the influence of the use of a model of Discovery Learning against learning outcomes of the thematic study on grade IV elementary school the country 35 South Pontianak. The method used is the method of experiments with forms of Pre-experimental designs and design one group pretest-postest-design. The population in this research is the whole grade IV elementary school South Pontianak 35 is totaled 96 students. Research using one class as a sample using simple random sampling technique that is by the way raffle. Data collection techniques used are measurement techniques with its data-collecting instruments in the form of a test in the form of multiple choice. Based on the results of the study, the average post-test of 71. Calculation t test was obtained tcount > t-table or 2,214 >1,670 then Ha received. Based on the results of the calculation of effect size (ES) was obtained ES of 0,47 including mediaum criteria are on beetwen 0,2 < ES < 0,8. So it can be concluded that there is an influence of the use of a model of Discovery Learning against learning outcomes on the thematic study grade IV elementary school the country 35 South Pontianak. Keywords: Influence, Discovery Learning Model, Learning Outcomes, Thematic